2020
DOI: 10.1177/1477153520979011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distraction, response mode and age on peripheral target detection to inform studies of lighting for driving

Abstract: It is expected that the detection of peripheral objects, a key visual task for safe driving, is affected by cognitive distraction, by observer age and by the manner in which action is undertaken following detection. An experiment was conducted to measure these effects, using a fixation cross and peripheral target discs displayed on a screen. The experiment was repeated with young (18–25 years) and old (60+years) age groups, with six distraction tasks, and with simple and choice response modes. The older group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Technol. 2024; 56: 283-294 attention 44 and, furthermore, when carried out in natural situations performance may be impaired by distraction 45 or by multi-tasking 46 ; these are likely to reduce the level of visual performance and reduce the impact of changes in those variables which directly affect vision. Further work is required to investigate their significance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technol. 2024; 56: 283-294 attention 44 and, furthermore, when carried out in natural situations performance may be impaired by distraction 45 or by multi-tasking 46 ; these are likely to reduce the level of visual performance and reduce the impact of changes in those variables which directly affect vision. Further work is required to investigate their significance.…”
Section: Discussionmentioning
confidence: 99%
“…The RVP model was established using tasks designed to focus on the visual component of task performance, such as numerical verification and detection of simple targets, 34,35 and performance of these tasks was a participant’s sole focus during trials. Facial evaluations, whether of identity or emotion, demand a greater degree of cognitive attention 44 and, furthermore, when carried out in natural situations performance may be impaired by distraction 45 or by multi-tasking 46 ; these are likely to reduce the level of visual performance and reduce the impact of changes in those variables which directly affect vision. Further work is required to investigate their significance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research investigates whether lighting conditions for pedestrians in urban environments are sufficient for the detections of obstacles [13,14] and identification of persons and recognition of emotional body language [15,16,17,18]. In addition to research describing urban spaces from the pedestrian's point of view, research related to cycling [19] and driving [2,20] and the transition between lit and unlit sections of a road [21] offers inspiration for how to design ratios of lighting in the current study. The potential to cause glare [22,23] and elements related to safety [24] should also be considered in the analysis of outdoor space.…”
Section: Framing Test Parametersmentioning
confidence: 99%
“…A recent review , conducted to inform research of lighting for driving (Fotios et al, 2020), concluded that conversing with passenger(s) was the most prevalent distraction from driving, confirming the findings of earlier work (Young & Salmon, 2012). For those studies included in the review (Table 1) the contexts in which distractions were identified can be categorised as distraction in use, as determined by roadside observation, or distraction at the time of an RTC, as determined using in-vehicle cameras, police reported crashes and self-report interviews when attending hospital after the RTC.…”
Section: Introductionmentioning
confidence: 99%